Effect of 5 different cervical collars on optic nerve sheath diameter: A randomized crossover trial - Ladny, Michal (Medicine (Baltimore), 2020)
BACKGROUND: There is considerable evidence that prolonged use of cervical collars potentially cause detrimental effects including increase in optic nerve sheath diameter (ONSD) among healthy volunteers. Different types of cervical collars immobilize cervical spine variably well and may presumably differently influence the venous compression and hence the intracranial pressure. We therefore aimed to evaluate the influence of cervical spine immobilization with 5 different types of cervical collars on ONSD measured noninvasively by ultrasound on healthy volunteers. METHODS: We conducted a randomized crossover trial including 60 adult healthy volunteers. Control assessment of the optic nerve sheath thickness was performed in both sagittal and transverse planes. Patient was placed supine on a transport stretcher, cervical collar was placed, and ONSD measurement was performed after 5 and 20 minutes. During the next days, the procedure was repeated with random allocation of participants and random cervical collar. RESULTS: Sixty healthy volunteers were included in our study. ONSD left diameter [mm] for the baseline was 3.8 [interquartile range (IQR): 3.65–3.93)] mm. Using AMBU after 5 min, ONSD was changed up to 4.505 (IQR 4.285–4.61; P < .001) mm. The largest change at 5 minutes and 20 minutes was using Philly 4.73 (IQR: 4.49–4.895; P < .001) and 4.925 (IQR: 4.65–5.06; P < .001), respectively. Necklite reported the lower change in ONSD: 3.92 (IQR: 3.795–4; P = 1.0) mm in 5 minutes and 3.995 (IQR: 3.875 – 4.1; P = 1.0) mm in 20 minutes. ONSD right diameter [mm] for the baseline was 3.8 (IQR 3.675–3.9) mm. Using AMBU after 5 minutes, ONSD was changed up to 4.5 (IQR 4.21–4.6) mm. The largest change at 5 minutes and 20 minutes was using Philly 4.705 (IQR 4.455–4.9) and 4.93 (IQR 4.645–5.075), respectively. Necklite reported the lower change in ONSD -33.9 (IQR 3.795–3.99) mm in 5 minutes and 3.995 (IQR 3.86–4.09) mm in 20 minutes. CONCLUSION: We report significant increase of ONSD from the baseline after cervical collar placement among healthy volunteers at 5 minutes and 20 minutes interval. In addition, no significant difference was noted between ONSD measurements at 5 and 20 minutes. Clinicians should take proactive steps to assess the actual need of cervical collar case by case basis. Nonetheless, when needed, Necklite moldable neck brace seems to be a reasonable option. Registration: ClinicalTrials database (www.clinicaltrials.gov, NCT03609879).